2020
DOI: 10.3390/rs12193174
|View full text |Cite
|
Sign up to set email alerts
|

Deep BLSTM-GRU Model for Monthly Rainfall Prediction: A Case Study of Simtokha, Bhutan

Abstract: Rainfall prediction is an important task due to the dependence of many people on it, especially in the agriculture sector. Prediction is difficult and even more complex due to the dynamic nature of rainfalls. In this study, we carry out monthly rainfall prediction over Simtokha a region in the capital of Bhutan, Thimphu. The rainfall data were obtained from the National Center of Hydrology and Meteorology Department (NCHM) of Bhutan. We study the predictive capability with Linear Regression, Multi-Layer Percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…In an experimental study to address the erratic rainfall patterns being predicted for Himalayan mountainous areas, Wangdi et al, conducted 100% throughfall exclusion and ambient control plots experiments to study the drought stresses on the ecology [36]. Chhetri used linear regression, multi-layer perceptron (MLP), convolutional neural network (CNN), long short-term memory (LSTM), gated recurrent unit (GRU), and bidirectional long short-term memory (BLSTM) to predict the monthly rainfall in Bhutan [37]. Using variable infiltration capacity (VIC) hydrological model, Sonessa et al found that the temperature variation greatly affects the runoff in northern part the country where elevation is more than 5000 m above sea level [38].…”
Section: Previous Studiesmentioning
confidence: 99%
“…In an experimental study to address the erratic rainfall patterns being predicted for Himalayan mountainous areas, Wangdi et al, conducted 100% throughfall exclusion and ambient control plots experiments to study the drought stresses on the ecology [36]. Chhetri used linear regression, multi-layer perceptron (MLP), convolutional neural network (CNN), long short-term memory (LSTM), gated recurrent unit (GRU), and bidirectional long short-term memory (BLSTM) to predict the monthly rainfall in Bhutan [37]. Using variable infiltration capacity (VIC) hydrological model, Sonessa et al found that the temperature variation greatly affects the runoff in northern part the country where elevation is more than 5000 m above sea level [38].…”
Section: Previous Studiesmentioning
confidence: 99%
“…When time scales on the order of months or longer are involved, datasets are typically much smaller than those involving shorter time scales. A broad range of ML methods are applied, from simple methods like multilinear regression (MLR) up to advanced neural networks models [13,[16][17][18]20,21,24,25,46,47,49,[59][60][61][62]. Because of the small data sets used, researchers often perform feature selection/reduction to avoid overfitting.…”
Section: Literature Review and Scope Of The Researchmentioning
confidence: 99%
“…Because of the small data sets used, researchers often perform feature selection/reduction to avoid overfitting. Most often, the selected features in the literature are combinations of features derived from previous time steps in the data, for example, a parameter at month n may be predicted based one or more parameter values taken from months previous to n [ [25][26][27]46,63].…”
Section: Literature Review and Scope Of The Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Kumar et al [ 68 ] used LSTM for forecasting monthly rainfall by using long sequential raw data for time-series analysis. Chhetri et al [ 69 ] presented a GRU-based model for rainfall prediction using weather parameters (temperature, rainfall, relative humidity, sunshine hour, and wind speed). Although advanced GRUs exhibit advantages in developing forecasting models, they have seldom been used in rainfall forecasting using radar reflectivities.…”
Section: Introductionmentioning
confidence: 99%